Violence against the elderly: a documentary study - Miriam Fernanda Sanches Alarcon; Daniela Garcia Damaceno; Carlos Alberto Lazarini; Luzmarina Aparecida Doretto Braccialli; Viviane Boacnin Yoneda Sponchiado; Maria José Sanches Marin (Universidade Federal do Ceará, 2019)
Objective: to associate the sociodemographic characteristics of elderly victims of violence and of the aggressors with types of violence. Methods: this is a cross-sectional, analytical, retrospective study developed in a police station. A total of 346 police reports were analyzed, and the statistical analyses of comparisons were made in the Statistical Package for the Social Sciences version 25.0.0.0. Results: type of violence was positively associated with area of the city, sex, marital status, schooling, age, place of occurrence, legal basis, and form of notification of the victim. There was a predominance of financial violence among men, while other types of violence, white skin, presence of a partner, and the victim's home as the place of occurrence predominated among women. There was a predominance of male aggressors. Conclusion: the police reports indicated the association of different sociodemographic data of victims and aggressors with the types of violence.